Information Security Risk Framework for Digital Transformation Technologies - Eduardo Stefani; Ivanir Costa; Marcos Antonio Gaspar; Roberto de Souza Goes; Rogerio Carlos Monteiro; Breno Ribeiro Petrili; Alexandre de Paula Pereira (Systems)
The increasing impact of digital technologies on society is marked by rapid and disruptive changes, including more efficient and modern processes, and is pushing companies to adopt digital solutions. However, companies have limited options, and can rarely avoid being affected by the speed and challenges introduced by digital technologies. Researchers have observed that, despite the advantages they bring, the cybersecurity risks associated with these technologies are not fully apparent. In this context, the present study aims to uncover the risks associated with using digital transformation technologies, which may lead to outcomes that fall short of initial expectations. As the research methodology, a systematic literature review was conducted involving a search for scientific articles in bibliographic databases in order to identify, organize, and classify these risks. This review offered visibility into the risks companies face when adopting digital technologies and provided a framework that highlights the most relevant risks. IT specialists validated these risks through a consistent questionnaire followed by application of the Cronbach’s alpha coefficient applied, aligning our systematic literature review with market realities regarding the risks that companies are exposed to when using digital technologies. As a contribution to both industry and academia, this work offers a framework that can support companies in their digital transformation journey by helping them to recognize and manage the cybersecurity risks associated with digital technologies. Future studies could expand on this framework by developing a model for risk prioritization and mitigation.